A High‐Volumetric‐Capacity Cathode Based on Interconnected Close‐Packed N‐Doped Porous Carbon Nanospheres for Long‐Life Lithium–Sulfur Batteries. Issue 22 (21st August 2017) - Hu, Cheng; Kirk, Caroline; Cai, Qiong; Cuadrado‐Collados, Carlos; Silvestre‐Albero, Joaquín; Rodríguez‐Reinoso, Francisco; Biggs, Mark James
Abstract: This study reports a Li–S battery cathode of high volumetric capacity enabled by novel micro‐ and mesostructuring. The cathode is based on monodisperse highly porous carbon nanospheres derived from a facile template‐ and surfactant‐free method. At the mesoscale, the nanospheres structure into interconnected close‐packed clusters of a few microns in extent, thus facilitating the fabrication of dense crack‐free high areal sulfur loading (5 mg cm −2 ) cathodes with high electrical conductivity and low cathode impedance. A combination of the nitrogen doping (5 wt%), high porosity (2.3 cm 3 g −1 ), and surface area (2900 m 2 g −1 ) at the microscale enables high sulfur immobilization and utilization. The cathode delivers among the best reported volumetric capacity to date, above typical Li‐ion areal capacity at 0.2 C over 200 cycles and low capacity fading of 0.1% per cycle at 0.5 C over 500 cycles. The compact cathode structure also ensures a low electrolyte requirement (6 µL mg −1 ), which aids a low overall cell weight, and further, among the best gravimetric capacities published to date as well. Abstract : Li–S battery cathodes providing among the best volumetric/gravimetric capacities reported to date are prepared using interconnected close‐packed N‐doped carbon nanospheres of high surface area and porosity. The novel close‐packed mesostructure and N‐doped highly porous microstructure enable simultaneously high sulfur density and utilization, excellent electrochemical impedance, long cycle‐life, and low electrolyte fraction, which all‐together leads to the outstanding volumetric/gravimetric capacities.